The Condition of Jewish Minority in Medieval Egypt: A Study of Jewish Ṣūfī’s Tractate al-Maqālat al-Ḥawḍiyya - Leonard Chrysostomos Epafras (Al-Jami'ah Research Centre, 2013)
During the reigns of Ayyūbids and Mamluks, a group of Jews developed a distinct Jewish spiritual system. The aim of this endeavor was to initiate spiritual renewal. The notable feature of the movement is the incorporation of substantial Ṣūfī elements into its spiritual system. By this unique feature the group might be tentatively called “Jewish Sufism.” This article explores the posture of this group and its understanding of Jewish diaspora and exile, particularly with regards Jewish minority status under Muslim rulers. As a study case, it focuses on the analysis of a Jewish Ṣūfī’s tractate entitled al-Maqālat al-Ḥawḍiyya (The Treatise of the Pool) written by ‘Abd Allāh ibn Ibrāhīm ibn Maymūn (1228-1263/65), the grandson of the prominent medieval Jewish philosopher and community leader (ra’īs al-yahūd), Mūsā ibn Maymūn (Moses Maimonides, 1135-1204). The article further argues that the tractate reflected Jewish struggle as minority under Islamic rulers and the contemporary socio-political upheaval. Besides the spiritual renewal, the discipline it endorsed was a way to cope with this minority status as well. Furthermore, the absorption of Sufism into Jewish spirituality may indicate a more dynamic interaction between Jews and Muslims in this period.[Pada masa pemerintahan dinasti Ayubi dan Mamluk di Mesir, sekelompok anggota komunitas Yahudi mengembangkan wacana spiritualitas yang unik demi pembaharuan hidup rohani mereka. Keunikan kelompok ini adalah karena dalam wacananya menyerap unsur-unsur Sufisme Islam. Gejala ini karena itu disebut Sufisme Yahudi. Artikel ini mengeksplorasi keberadaan kelompok tersebut dan pemahaman mereka akan diaspora Yahudi, terutama dalam kaitannya dengan kondisi minoritas mereka. Sebagai studi kasusnya adalah traktat spiritual bertajuk al-Maqālat al-Ḥawḍiyya (Traktat tentang Kolam) yang ditulis oleh ‘Abd Allāh ibn Ibrāhīm ibn Maymūn (1128-1263/65), cucu dari filsuf dan pemimpin Yahudi Abad Pertengahan (ra’īs al-yahūd), Mūsā ibn Maymūn (Moses Maimonides, 1135-1204). Artikel ini mengungkapkan bahwa karya tersebut mencerminkan pergumulan kaum Yahudi sebagai minoritas dan ketegangan sosio-politis yang mereka alami. Disiplin rohani yang disarankannya juga dimaksudkan untuk mengatasi status minoritas tersebut. Lebih dari itu, penyerapan unsur Sufi ke dalam spiritualitas Yahudi ini mendorong ke arah hubungan Yahudi dan Muslim yang lebih dinamis pada masa itu.]